161 - PILATES PRACTITIONERS' BODY IMAGE ANALYSIS (Fiep Bulletin - online, 2011)
The Pilates Method integrates body and mind; its approach is systemic and considers the individual's physical and emotional aspects. The concept of body image is a multidimensional construction of an individual. The aim of this study is to identify and compare the body image of Pilates practitioners (group A) and individuals who do not have a physical activity (group B). In order to accomplish this, the "Body Shape Questionnaire" (BSQ) was used with 26 women – from 20 to 40 years old. The T-Student test was used for inferential analysis. Based on the data obtained, we could observe that there has not been any degree of dissatisfaction related to body image.
Keywords: body image; Pilates Method; physical activity